A heterobimetallic cumulenic μ-carbido complex. Issue 15 (29th January 2020) - Hill, Anthony F.; Watson, Lachlan J.
Abstract : Cleavage of a selenocarbonyl ligand in [W(CSe)(NO)(CO)(Tp*)] by [Re(THF)(CO)2 (Cp)] provides heterobimetallic cumulenic μ-carbido and μ-selenido complexes. Abstract : The reaction [W(CSe)(CO)2 (Tp*)]NEt4 (Tp* = hydrotris(dimethylpyrazolyl)borate) with N -methyl- N -nitroso-4-toluenesulfonamide affords the nitrosyl complex [W(CSe)(CO)(NO)(Tp*)] which on treatment with excess [Re(THF)(CO)2 (η-C5 H5 )] affords the cumuenic μ-carbido complex [WRe(μ-C)(CO)3 (NO)(Tp*)(η-C5 H5 )] in addition to the μ-selenido complex [Re2 (μ-Se)(CO)4 (η-C5 H5 )2 ].